Identification of the lydiamycin biosynthetic gene cluster in a plant pathogen guides structural revision and identification of molecular target - Jonathan J. Ford; Javier Santos-Aberturas; Edward S. Hems; Joseph W. Sallmen; Lena A. K. Bögeholz; Guy Polturak; Anne Osbourn; Joseph A. Wright; Marina V. Rodnina; Danny Vereecke; Isolde M. Francis; Andrew W. Truman (Proceedings of the National Academy of Sciences, 2025)
The natural products actinonin and matlystatin feature an N -hydroxy-2-pentyl-succinamyl (HPS) chemophore that facilitates metal chelation and confers their metalloproteinase inhibitory activity. Actinonin is the most potent natural inhibitor of peptide deformylase (PDF) and exerts antimicrobial and herbicidal bioactivity by disrupting protein synthesis. Here, we used a genomics-led approach to identify candidate biosynthetic gene clusters (BGCs) hypothesized to produce HPS-containing natural products. We show that one of these BGCs is on the pathogenicity megaplasmid of the plant pathogen Rhodococcus fascians and produces lydiamycin A, a macrocyclic pentapeptide. The presence of genes predicted to make an HPS-like chemophore informed the structural recharacterization of lydiamycin via NMR and crystallography to show that it features a rare 2-pentyl-succinyl chemophore. We demonstrate that lydiamycin A inhibits bacterial PDF in vitro and show that a cluster-situated PDF gene confers resistance to lydiamycin A, representing an uncommon self-immunity mechanism associated with the production of a PDF inhibitor . In planta competition assays showed that lydiamycin enhances the fitness of R. fascians during plant colonization. This study highlights how a BGC can inform the structure, biochemical target, and ecological function of a natural product.